A Dynamic Process Model of Private Politics - McDonnell, Mary-Hunter; King, Brayden G; Soule, Sarah A. (American Sociological Review, 2015)
This project explores whether and how corporations become more receptive to social activist challenges over time. Drawing from social movement theory, we suggest a dynamic process through which contentious interactions lead to increased receptivity. We argue that when firms are chronically targeted by social activists, they respond defensively by adopting strategic management devices that help them better manage social issues and demonstrate their normative appropriateness. These defensive devices have the incidental effect of empowering independent monitors and increasing corporate accountability, which in turn increase a firm’s receptivity to future activist challenges. We test our theory using a unique longitudinal dataset that tracks contentious attacks and the adoption of social management devices among a population of 300 large firms from 1993 to 2009.